Relationship between C677T Methylenetetrahydrofolate Reductase Gene Polymorphism and Homocysteine in Cerebral Palsy - Gamayani, Uni; Machfoed, M. Hasan; Idjradinata, Ponpon; Achmad, Tri Hanggono (International Journal of Integrated Health Sciences, 2016)
Objective: To observe the relationship between methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism and homocysteine levels in cerebral palsy (CP) children. Methods: This cross-sectional study was conducted in several hospitals, school for children with special needs, and rehabilitation centers in Bandung from March to November 2014, on children with CP aged 4–14 years who met the inclusion criteria. Genotyping was performed using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) and direct sequencing. Homocysteine serum level was measured using chemiluminescent microparticle immunoassay (CMIA) method. Statistical analysis was conducted using t test. Results: In this study, 150 CP children had MTHFR C677T gene polymorphism with a frequency of 18%, consisting of TT homozygotes (4%), CT heterozygotes (14%), and T allele (11%. The mean serum level of homocysteine in CP with C677T MTHFR gene polymorphism was 8.22 (±1.89) µmol/L, higher than those without polymorphism (p=0.046). Conclusions: A relationship between MTHFR C677T gene polymorphism and homocysteine level in children with cerebral palsy is found in this study. Keywords: Cerebral palsy, homocysteine, methylenetetrahydrofolate reductase polymorphism DOI: 10.15850/ijihs.v4n1.682